Arabic Linguistics of OT as Analytical Approach for Grammatical Error in Quran: A Preliminary Concept - Mohd Nizwan Musling; Zainur Rijal Abdul Razak (Human Resource Management Academic Research Society, 2024)
Vol 12, Issue 4